Mechanical Behaviors of Carbon Nanotubes : Theoretical and Numerical Approaches - Liew, K. M. (Micro & nano technologies., 2017)
This book presents various theoretical and numerical studies on mechanical behaviors of carbon nanotubes. The main theoretical aspects included in the book contain classical molecular dynamics simulation, atomistic-continuum theory, atomic finite element method, continuum plate, nonlocal continuum plate, and shell models. Detailed coverage is also given to structural and elastic properties, trace of large deformation, buckling and post-buckling behaviors, fracture, vibration characteristics, wave propagation, and the most promising engineering applications.